2004
DOI: 10.1007/s00253-003-1545-7
|View full text |Cite
|
Sign up to set email alerts
|

Lincomycin, clindamycin and their applications

Abstract: Lincomycin and clindamycin are lincosamide antibiotics used in clinical practice. Both antibiotics are bacteriostatic and inhibit protein synthesis in sensitive bacteria. They may even be bactericidal at the higher concentrations that can be reached in vivo. Clindamycin is usually more active than lincomycin in the treatment of bacterial infections, in particular those caused by anaerobic species; and it can also be used for the treatment of important protozoal diseases, e.g. malaria, most effectively in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(66 citation statements)
references
References 65 publications
1
58
1
Order By: Relevance
“…NMR studies revealed that this antibiotic compared with lincomycin exhibits higher affinity for the ribosome (3), in agreement with in vivo studies carried out in common pathogenic bacteria including Escherichia coli (1). In another study, however, the in vitro affinity of lincomycin to E. coli ribosomes was reported to be higher than that of clindamycin (4).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…NMR studies revealed that this antibiotic compared with lincomycin exhibits higher affinity for the ribosome (3), in agreement with in vivo studies carried out in common pathogenic bacteria including Escherichia coli (1). In another study, however, the in vitro affinity of lincomycin to E. coli ribosomes was reported to be higher than that of clindamycin (4).…”
supporting
confidence: 72%
“…1) are lincosamides, still used as therapeutic agents in human diseases and some animal infections. Clindamycin, a semisynthetic derivative of lincomycin (7(S)-chloro-7-deoxylincomycin), is usually more active than the parent compound in the treatment of bacterial infections, in particular those caused by anaerobic species (1).…”
mentioning
confidence: 99%
“…When the drug was used alone, rapid emergence of resistance limited its use, except in association with another antistaphylococcal drug [20]. Clindamycin is a lincosamide antibiotic active against Gram-positive cocci and most anaerobic bacteria [21]. One trial found topical clindamycin superior to its vehicle [22], while another showed no difference between topical clindamycin and systemic tetracycline [23].…”
Section: Discussionmentioning
confidence: 99%
“…The selected antibiotics range in their mode of antimicrobial activity including, inhibition of protein synthesis by preventing the binding of aminoacyl-t-RNA to the ribosomyl 30S subunit (tetracycline) [30] or by targeting the 23S rRNA by binding to the 50S ribosomal subunit (clindamycin), [31] inhibiting cell wall synthesis (vancomycin), [32] inactivating protein translation on the 50S ribosome during the peptidyl transferase step (chloramphenicol), [33] inhibiting DNA synthesis (ofloxacin), [34] inhibiting RNA synthesis by binding to RNA polymerase (rifampicin), [35] and interfering with cell wall permeability by binding to lipids on bacterial cytoplasmic membrane (colistin). [36] Combinations consisting of a cyclooctapeptide and one of these antibiotics, at their respective MICs, were tested [11] against E. coli and/or S. aureus based on the selectivity of the antibiotic for these bacteria.…”
Section: Synergistic Testingmentioning
confidence: 99%